PENGARUH EFEKTIVITAS MODERNISASI.SISTEM. ADMINISTRASI PERPAJAKAN, TINGKAT PEMAHAMAN PERATURAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI ( Studi Survey dengan Wajib.Pajak.Orang.Pribadi yang Terdaftar.di.Kantor. - Alwi Raninda Sari; Dewi Rejeki (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
This research aims to determine the compliance of individual taxpayers in the West Bekasi City Area, using several variables, such as the effectiveness of the modernization of the tax administration system, the level of understanding of tax regulations, and tax sanctions. The method used in this research is quantitative methods. Quantitative methods is a method that analyzes numbers or calculating primary data (questionnaires) obtained from the respondents.The results of this research prove that the variables, namely the effectiveness of the modernization of the tax administration system and the level of understanding of taxation regulations has a positive and significant effect, while for the tax sanctions variable it proves that there is no significant effect on taxpayer compliance in implementing taxation